Theories of place, change and induced change for tree-crop-based agroforestry - Noordwijk, M. van (World Agroforestry Centre, 2021)
Agroforestry with a strong market-oriented component of tree crops but also supporting local agroecosystem functions can be analysed and understood in multiple ways, building on many disciplinary traditions and using their terminology and concepts. Characterization of context and choices, plus understanding relationships and feedbacks is essential for appreciating ‘options in context’ and the way these change over time. Beyond observer roles, active engagement as agent of induced change to help make the world a better place has since long been the ambition of advocates of agroforestry. As a background to such endeavours , this publication introduces more than one hundred aspects, visually and with a short text, providing references to more specialized literature. Aspects include: A) Characterization of structure in existing land use can lead to a Theory of Place (ToP: patterns answering what?, where?, who? questions), B) Diagnosis of functions influenced by changing practices and systems can lead to a Theory of Change (ToC: patterns in answering how?, why?, since when?, so what? and who cares?), C) Assessments of leverage points for adaptive, transformative and re-imaginative change can lead to a project-design Theory of Induced Change (ToIC), D) Research methods for ecological, agronomic, social, economic and policy-oriented research require clarity on units of analysis and scale relations of observable properties in relation to questions and hypotheses, E) Guidance on how research methods need to match the stage of public issue cycle debate to contribute to policy reform.